THE INFLUENCE OF DIGITAL MARKETING, GAMIFICATION, AND BRAND IMAGE ON GEN-Z CONSUMER LOYALITY ON SHOPEE E-COMMERCE PLATFORMS - Adhelia Cahya Puspita; Rita Ambarwati Sukmono; Mochamad Rizal Yulianto (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study examines the influence of digital marketing, gamification, and brand image on Generation Z consumer loyalty in the Shopee e-commerce platform in Indonesia. As digital natives, Gen-Z consumers prefer interactive, creative, and technology-driven shopping experiences. Method: Using a descriptive quantitative approach, data were collected through an online Likert-scale questionnaire from 100–150 respondents selected via simple random sampling. The Slovin formula was applied to determine sample size. Data analysis employed Structural Equation Modeling-Partial Least Square (SEM-PLS), including tests of validity, reliability, R², f², and bootstrapping.  Results:  Results show that digital marketing, gamification, and brand image together explain 84.6% of the variance in Gen-Z loyalty. Gamification and brand image significantly affect loyalty, with gamification being the most dominant factor. In contrast, digital marketing has a positive but insignificant effect, indicating that Gen-Z is more selective toward repetitive or impersonal promotional content.  Novelty: These findings highlight the importance of interactive features and strong brand image in building sustainable consumer loyalty.